Urban marginality, religious liminality, and the black poor - Smith, R. Drew (HTS teologiese studies, 2015)
While many persons within westernised or westernising nations such as the United States of America and South Africa continue to place importance on matters of faith, a growing number of those persons approach matters of faith informally rather than formally and individually rather than institutionally. The implications of this are that among 21st century populations informal religious formation may be as important as or more important than the formation taking place via formal religious channels. A central emphasis of this article is that this is especially true among more socially marginalised populations, not simply because they may not enjoy the same level of access to formal institutions, but also because they may regard those institutions as spiritually and culturally restrictive and exclusionary. The contributions of the article are, firstly, its use of original and unique survey data generated from neighbourhood studies the author directed in low-income contexts within several U.S. cities and within Pretoria, South Africa, and, secondly, its analysis of informal ways the urban poor engage Christian ideas and practices − an aspect of urban religion that has not received adequate scholarly attention.